Fibrous epulis - case report - Marina Radanović; Slavoljub Tomić; Tanja Ivanović; Ana Cicmil; Jovana Hrisa Samardžija; Srdjan Radanović; Jelena Lečić (Биомедицинска истраживања, 2022)
Introduction: . Epulis is a change in gingival tissue that occurs under the influence of chronic irritation. Histologically, there are several different types of epulis. Fibrous epulis is benign tumor of gingiva that most of ten occurs in interdental papilla area as a result of local irritation (in adequate restorative fillings, carious teeth, subgingival deposits or the combination of them). The aim of this paper is to present a clinical case of fibrous epulis. Case report. A 25-year-old girl reported to the Specialist Center for Dentistry in Foca. Clinical examination revealed a gingival tissue en largement in the area of the upper jaw central incisors with speech and chewing function disturbances. Intraoral examination revealed a change above the level of gingiva, reddish-pink in color with smooth surface texture and soft consistency. The size of the change was 1 x 1.5 cm. It was connected to the interdental gingiva between teeth 12 and 21 by a narrower base. Clinically, a significant amount of soft and hard dental deposits surrounded the remaining teeth. Remaining gingiva was swollen, red, bleeding on provocation. The anamnesis did not con firm the presence of other acute and chronic diseases. The patient was not pregnant. She was informed about clinical condition assessment, as well as possible therapeutic procedures. Our patient was treated with non-surgical periodontal therapy and surgical excision of the enlarge ment. After histopathological examination of the removed tissue, the diagnosis was made: "Fibrous epulis cum ulceration". Conclusion: Clinical examination is insufficient for definite diagnosis. Therefore, a histopathological examination of the tissue is mandatory for fibrous epulis definite diagnosis. Treatment of choice is surgical ex cision of the enlargement and removal of predisposing factors to avoid recurrence.
Keywords: gingiva; epulis; central incisors